Concerning the question of the origin and development of urinary symptoms among the patients with diabetes mellitus type 1 and 2 - Kuznetsova, E.; Gozhenko, A.; Saiensus, M. (Journal of Education, Health and Sport, 2024)
Analyzed disorders of the kidney in 102 patients with diabetes mellitus type 1 and 2, who were hospitalized at the Odessa Regional Clinical Medical Center during 2012-2013 to take into account general clinical research, clinical diagnosis, comorbidities and complications of diabetes, as well as laboratory and instrumental methods of investigation, which included a definition HBAlc, fasting glucose and dynamics in 8.00-12.00-16.00-19.00, glycosuria and acetonuria of daily urine, complete blood count, urinalysis, liver, kidney tests, ECG, ultrasound of the abdomen and kidney. The results of the functional features of the kidney in patients with diabetes type 1 and 2 allow to conclude that the urinary syndrome is observed in the majority of cases, with selective proteinuria without other formed elements in the urinary sediment is found in 76% of cases, and the addition of 95% of pyuria cases shows comorbidities - chronic pyelonephritis, which occurs in 52% of patients with diabetes mellitus. Of the 90 patients who were diagnosed with urinary syndrome, 98% were able to hronichekoy hyperglycemia demonstrated with HbA1c levels of 8% - 14.6% and the level of glycosuria at admission, which was within 5 - 415 mmol l. The degree of renal damage, estimated clinical and laboratory methods in patients, and the rate of progression of diabetic nephropathy in patients was different. According to studies, 30% of patients with type 1 diabetes and 25% to 40% of patients with type 2 diabetes development and progression of diabetic nephropathy is not directly dependent on the level of glycemia.